Introduction to geographic information systems - Chang, Kang-Tsung (McGraw-Hill Education, 2016)
Introduction to Geographic Information Systems, 8th edition is designed to provide students in a first or second GIS course with a solid foundation in both GIS concepts and the use of GIS. Introduction to GIS strikes a careful balance between GIS concepts and hands-on applications. The main portion of the chapter presents GIS terms and concepts and helps students learn how each one fits into a complete GIS system. At the end of each chapter, an application section with 2-7 tasks presents students with actual GIS exercises and the necessary data to solve the problem.